2020
DOI: 10.1016/j.psfr.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Why do people come to support a highly controversial law? Manipulating the clarity and coherence of a law can shape individuals’ perception and approval

Abstract: Pourquoi les gens appuient-ils une loi controversée ? Manipuler la clarté et la cohérence d'une loi pour façonner la perception et l'approbation des individus Why do people come to support a highly controversial law? Manipulating the clarity and coherence of a law can shape individuals' perception and approval

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Before presenting our theoretical reasoning in this regard, we review the literature of each concept in turn. This is because perceived clarity and perceived coherence emerged from different theoretical perspectives and that it is just recently that they have been theorized to be influential conjointly (Kleinlogel, Nugier, Pelletier‐Dumas, de la Sablonnière, & Guimond, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before presenting our theoretical reasoning in this regard, we review the literature of each concept in turn. This is because perceived clarity and perceived coherence emerged from different theoretical perspectives and that it is just recently that they have been theorized to be influential conjointly (Kleinlogel, Nugier, Pelletier‐Dumas, de la Sablonnière, & Guimond, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that perceived clarity and perceived coherence independently influence perceived cultural norms. However, initial evidence (Kleinlogel et al, ) revealed an interaction effect between the perceived clarity and the perceived coherence of a proposed law predicting individuals’ personal attitudes toward this law. For instance, it was observed in the French context that the perceived coherence was associated with greater support when the perceived clarity was high, as expected.…”
Section: Introductionmentioning
confidence: 99%